2023
DOI: 10.3389/fmicb.2023.1201201
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and anti-biofilm activities of probiotic Lactobacillus plantarum against Listeria monocytogenes isolated from milk, chicken and pregnant women

Abstract: Listeria monocytogenes (L. monocytogenes) is a foodborne pathogen that poses significant risks to public health and food safety. The present study aimed to identify the presence of Listeria spp. in various samples, including pasteurized milk, chicken fillets, and stool samples from pregnant women in Sharkia Governorate, Egypt. Additionally, the study identified the serotypes, virulence-associated genes, antimicrobial resistance patterns, and biofilm formation in L. monocytogenes isolates. Moreover, the antibac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…An ELISA reader (Sunrise R4, Tecan) calculated the OD of the biofilm at 590 nm after the negative control (OD NC ) was set at zero. The negative and positive controls used were sanitized medium only and the working solution, respectively ( Pierce et al., 2008 ; Abou Elez et al., 2023 ). The rate (%) of biofilm inhibition was measured through the subsequent equation:…”
Section: Methodsmentioning
confidence: 99%
“…An ELISA reader (Sunrise R4, Tecan) calculated the OD of the biofilm at 590 nm after the negative control (OD NC ) was set at zero. The negative and positive controls used were sanitized medium only and the working solution, respectively ( Pierce et al., 2008 ; Abou Elez et al., 2023 ). The rate (%) of biofilm inhibition was measured through the subsequent equation:…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, in vivo studies in rats demonstrated that probiotics could enhance host resistance against oral L. monocytogenes infection [68]. However, it has been found that probiotics can suppress L. monocytogenes colonization to some extent, but never prevent it [69]. Thus, the use of probiotics or their combination, as well as their antibacterial metabolites, has considerable potential in the agri-food industry.…”
Section: Disk Diffusion Testmentioning
confidence: 99%